Developing a Psychiatry Residency Program in a Low- and Middle-Income Country: Botswana’s Experience - Philip R. Opondo; Anthony A. Olashore; James O. Ayugi; Masego B. Kebaetse; Keneilwe Molebatsi (Journal of Medical Education and Curricular Development)
Like many other low- and middle-income countries, Botswana has struggled to address the shortage of doctors, particularly specialists. In 2009, the country’s first medical school offering an undergraduate medical program was established. A needs and feasibility assessment was conducted with relevant stakeholders to explore the need for specialty training programs in all medical school departments. As a result, three residency programs were established a year after the undergraduate program, but psychiatry was not included in this first crop of residency programs. Existing strengths in the university and healthcare systems were leveraged to successfully establish a four-year Master of Medicine residency program in psychiatry, which began in January 2020. The program aims to produce psychiatrists who are familiar with the local mental health needs. The first batch of students completed their training in December 2023. This paper reflects on and describes the development of a psychiatry residency program in Botswana and contributes a process grounded in educational program development models and educational theories that others can utilize. Botswana’s experience may be helpful to other low- and middle-income countries, particularly in sub-Saharan Africa, that want to establish and run a locally developed residency program in psychiatry.